Do Politically Connected Directors Affect Fraudulent Financial Reporting? Evidence from Nigeria Listed Firms. - Ashafoke, Tina Oghenekome; Aderin, Adeyemi (The Journal of Accounting and Management, 2023)
This study examined the impact of politically connected directors on fraudulent financial reporting for selected listed firms in Nigeria. An ex-post-facto research design data was adopted for the study. A sample size of 80 listed firms from the Nigerian Stock Exchange group was selected from 2014 to 2020. Panel logistic regression was utilised for the study and testing of the hypotheses. The study showed that politically connected directors do not effectively determine the probability that a company would engage in fraudulent financial reporting. However, the study director’s overconfidence had a significant positive relationship with fraudulent financial reporting. Director’s financial expertise and directors ownership exhibited an insignificant influence on fraudulent financial reporting. However, the director’s compensation revealed a significant negative relationship with fraudulent financial reporting at a p-value of 5% significant level. The study recommended that more politically connected directors should be appointed to the board. It is expected that a higher percentage of politically connected directors will report a significant negative relationship. It also recommends that more directors with financial expertise should be appointed to the board. As this will help to significantly reduce the likelihood of fraudulent financial reporting.